ANALISIS HUBUNGAN BEBAN KERJA MENTAL DENGAN STRES KERJA DI INSTALASI CSSD RUMAH SAKIT UMUM HAJI SURABAYA - Fahamsyah, Dikky (Jurnal keselamatan dan kesehatan kerja = The Indonesian journal of occupational safety and health, 2017)
ABSTRACT Mental workload is a workload which is the difference between the demands of the workload of a task with a maximum capacity load of a person's mental condition motivated, excessive workload will lead to the incident  of stress. Work stress is distress experienced by employees when facing job. The purpose of this research was  to study the picture of mental workload and stress on employees who work in CSSD Installation General Hospital Haji Surabaya. This research was a descriptive cross sectional approach. The subjects of this research  were employees in the Installation CSSD General Hospital Haji Surabaya. The variables of this research were the mental workload and job stress. Primary data was collected using questionnaires and observation. Secondary data obtained from the General Hospital Haji Surabaya. Furthermore the data was processed by descriptive and described in narrative form. The results  showed that the CSSD employees experiencing mental workload which was divided into seven employees experiencing medium metal workload and  four employees  experiencing low mental workload . In addition there was a relationship between mental workload with the incidence of workplace stress. overall it can be described that mental workload and workplace stress were in the medium level. It was recommended that employees  can used the time off well  and getting used to exercise to increase endurance. Keywoard : mental workload, workplace stress, installation sterilization center